Bibliography of Aleyrodidae II. - Butani, Dhamo K. (Contributions to Entomology = Beiträge zur Entomologie, 1970)
Trehan and Butani (1960) published a comprehensive bibliography listing 998 references of the Aleyrodidae. This is a supplement to that treatise.